Systematic of Bottom Plants, Algae and Them the Importance of Bacteria in Nature (Journal of Architectural Design, 2022)
Bottom plants, Thallophyta - plants with a simple structure. Plants body is not divided into roots, stems and leaves. Plants originated in the early stages of the organic world. They are adapted to live in watery environments or dry places. In the course of evolution, some of them have not developed much, and until now some of them have preserved their simple structure. Beneficial plants are single-celled, colony-forming and multicellular organisms, and their bodies are called "cattana" or "thallom" because their bodies are not divided into tissues and organs.